Alimento vivo enriquecido con ácidos grasos para el desarrollo larvario de peces - Rivera Narváez, Carlos Mario; Botero Aguirre, Mónica (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary The larvae nutrition represents one of the main problems in the great scale production of fish. The primary objective of this review is to enlarge the knowledge of the factors that take part in the organic and digestive development of fish and the way these factors can affect their growth and survival. The development of digestive tract in the larvae of fish is conditioned by anatomo-physiological aspects that allow pos-larvae to adapt biochemical and histologically to periods of transition between the end of the reabsorption of the yolk sac and the beginning of consumption of live feed, and from the consumption of live feed to a balanced commercial diet. The species used in the first feeding of post-larvae affect their survival and development. An inadequate provision could cause a high mortality due to the fact that the zooplankter species that proliferate everywhere not always satisfy the growing fish nutritional requirements, their volume growth is inferior to the required volume and, on top of that, a wrong production handling favors the proliferation of depredating planktonic species. Bearing in mind that one of the main nutrients t0hat live feed contributes, are the non-saturated and polyunsaturated fatty acids, nutritional deficiencies in the live feed can be complemented with the enrichment of fatty acids, which are essential components in the processes of pigmentation, production of prostaglandins and immunological defenses, plus retinal development required to improve visual capacity and sharpness, among others.